2009
DOI: 10.1007/s00431-009-1113-y
|View full text |Cite
|
Sign up to set email alerts
|

Use of self-heating gel mattresses eliminates admission hypothermia in infants born below 28 weeks gestation

Abstract: Self-heating acetate gel mattresses are highly effective in reducing admission hypothermia in infants born at or below 28 weeks gestation. The use of these mattresses is associated with a significant increase in hyperthermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…10 In practice the activated EM acts as an external heat source so that when infants are placed on a warm EM, they absorb heat by conduction through the surface of their skin in contact with the EM. In 2 retrospective studies, less hypothermia was observed when infants in PBs were placed on EMs in the DR compared with previous cohorts when EMs were not used (23% vs 3% 11 and 69% vs 26% 12 ). In both studies, the rate of hyperthermia increased with the addition of the EM (50% 11 and 28% 12 ).…”
Section: Discussionmentioning
confidence: 91%
“…10 In practice the activated EM acts as an external heat source so that when infants are placed on a warm EM, they absorb heat by conduction through the surface of their skin in contact with the EM. In 2 retrospective studies, less hypothermia was observed when infants in PBs were placed on EMs in the DR compared with previous cohorts when EMs were not used (23% vs 3% 11 and 69% vs 26% 12 ). In both studies, the rate of hyperthermia increased with the addition of the EM (50% 11 and 28% 12 ).…”
Section: Discussionmentioning
confidence: 91%
“…18,25,29 Furthermore, the large sample size and our consistent rates of normothermia indicate that these results did not occur by chance. From a safety perspective, our ability to prevent hypothermia without incurring hyperthermia or other obvious complications of resuscitation is important, because this has been a concern in some previous studies, 20,25,26,30 and it may also contribute to morbidity. 31 Qualitative, unplanned observations of staff dynamics raised the possibility that standardizing temperature measurements, which was aimed at maximizing accuracy and avoiding biases, serendipitously became an intangible intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Various combinations of these strategies may be reasonable to prevent hypothermia in infants born at less than 32 weeks of gestation (Class IIb, LOE B-R, B-NR, C-LD). Compared with plastic wrap and radiant warmer, the addition of a thermal mattress, [66][67][68][69][70] warmed humidified gases, 71,72 and increased room temperature plus cap plus thermal mattress 55,57,59,73 were all effective in reducing hypothermia. For all the studies, hyperthermia was a concern, but harm was not shown.…”
Section: Nrp 599mentioning
confidence: 99%